Analysis of the Application of Good Manufacturing Practices (GMP) for Bread Products at CV Sari Mart, Poasia District, Kendari City - Munawir Diraeli; Sarinah Sarinah; Rosmawaty Rosmawaty (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian, 2022)
Every food producer must have qualified according to standards so that the food produced is safe for consumption. The study aims to identify the application of Good Manufacturing Practices (GMP) for bakery products at CV Sari Mart, Poasia sub-district, Kendari city, and provide recommendations for the best improvements related to the problems of implementing Good Manufacturing Practices (GMP) at CV Sari Mart. Data collection comes from direct observations, interviews, and evaluations carried out by observing all aspects of Good Manufacturing Practices (GMP) based on the regulation of the Ministry of Industry of the Republic of Indonesia No. 75 of 2010). Identification of the implementation of Good Manufacturing Practices (GMP) at CV Sari Mart based on the Minister of Industry Regulation on Good Processed Food Production Methods (CPPOB) with a checklist gap getting a total of 60% of 18 parameters, which means CV Sari Mart still has to improve to meet the requirements of GMP standards according to Regulations The Minister of Industry of the Republic of Indonesia Number 75/M-IND/PER/7/2010 concerning guidelines for good processed food production.